Understanding the relationship of academic motivation and social support in graduate nursing education in Egypt - Mona Metwally El-Sayed; Samah Mohamed Taha; Eman Sameh AbdElhay; Manal Mohammed Hawash (BMC, 2024)
Abstract Background Obtaining a postgraduate nursing education in Egypt requires substantial resources, including a robust academic drive and supportive relationships. These resources help students overcome challenges and navigate their educational journey. This study examines the relationship between academic motivation and social support among nursing graduate students. Design A cross-sectional survey was conducted at two nursing colleges in Egypt, involving 410 randomly selected graduate students. Measures The Academic Motivation Scale-College Version (AMS-C 28) and the Multidimensional Scale of Perceived Social Support (MSPSS) were used. Findings Findings revealed a statistically significant positive relationship between academic motivation and perceived social support (r = 0.515, p < 0.001). Hierarchical regression analysis revealed that 12.9% (Adjusted R² = 0.129) of the variance in academic motivation could be explained by perceived social support and level of education. Conclusion This study pinpointed intrinsic motivation as the primary impetus for graduate nursing students. Robust social support and active participation in social and recreational activities were also significant motivators. Nursing education programs can enhance intrinsic motivation by integrating authentic learning experiences, providing empowering mentorship, offering condensed doctoral programs, and ensuring substantial peer support. The exploration of the role of novelty in graduate nursing education, facilitated by innovative teaching methods such as collaborative virtual reality simulations, gamification, and team-based research projects, can be advantageous. Building robust social networks is vital for establishing a supportive and motivating learning environment for nursing graduates in Egypt.